Study of nodular cast iron austenitic matrix - Dionicio, Eusebio (2013)
Nodular cast iron austempered has superior mechanical properties than other family members of nodular cast iron in relation to properties like machinability, tensile strength, wear resistance, toughness and ductility.The first stage of this research seeks nodular cast iron base material of a specific composition. For this purpose, the nodular cast iron is obtained in a 10 kg crucible furnace using both heat energy of propane gas (LPG) and magnesium alloy as a catalytic agent which is added at the bottom of the molten material as inoculant silicon (ferrosilicon). The liquid metal mold casting sand is wedge shaped. The material microstructure evaluation was performed in both tin and thick areas as follows: a) On the wedge area of minor thickness, fringe pelletizing graphite, fringes with pearlite matrix and steatite were detected. b) On the wedge area of major thickness, graphite fringes with some nodules in pearlitic matrix was observed.